2016
DOI: 10.15640/jmm.v3n2a7
|View full text |Cite
|
Sign up to set email alerts
|

Public Relations as Part of Integrated Communication of an Enterprise-Consumer Oriented On

Abstract: Purpose: This research aims to identify key factors that influence physicians' drug selection decisions as well as the main sources of information for physicians about new drugs and the most effective "reminder methods" used by pharmaceutical sales representatives. This study fills a gap within the existing literature by identifying the most important factors that affect physicians' drug selection decisions in Saudi Arabia Design/methodology/approach: A survey was conducted in the Western region of Saudi Arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…These findings show that the Museum uses publications adequately, as the majority of visitors agree that the publication tools are used adequately. This reiterates Ukaj's (2014) finding that product messages to the visitors should be harmonised, consistent and complimentary to one another without leaving any space for contradiction. In the light of this, the Apartheid Museum's various publication messages should be integrated and the messages must be consistent, truthful and centrally controlled in a manner that promotes the Museum offerings.…”
Section: Conclusion On Research Objectives One: To Explore the Visito...supporting
confidence: 61%
See 1 more Smart Citation
“…These findings show that the Museum uses publications adequately, as the majority of visitors agree that the publication tools are used adequately. This reiterates Ukaj's (2014) finding that product messages to the visitors should be harmonised, consistent and complimentary to one another without leaving any space for contradiction. In the light of this, the Apartheid Museum's various publication messages should be integrated and the messages must be consistent, truthful and centrally controlled in a manner that promotes the Museum offerings.…”
Section: Conclusion On Research Objectives One: To Explore the Visito...supporting
confidence: 61%
“…A study by Papasolomou et al (2014:7) found that well-executed strategic marketing public relations is a necessity to a product survival. A study by Ukaj (2014) showed that communication to consumers must be harmonised, consistent, and complementary to each other leaving no space for contradictions.…”
Section: Defining Mprmentioning
confidence: 99%
“…The design of the search strategy was based on a preliminary review of the relevant articles and consultation with marketing communication scholars. Each search string consisted of the following three parts: e-cigarette and its variations in terminology, communication channels, and marketing communication strategies ( Figure 1 ), which referred to Kotler and Keller’s marketing communication mix of strategies [ 25 ] and integrated other marketing strategy literature [ 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Marketing communication strategy was coded into the following five categories: advertising, public relations, sales promotion, personal selling, and direct marketing. These strategies were based on Kotler and Keller’s categorization and definitions of marketing communication strategies [ 25 ] and revised after integrating further literature [ 26 , 27 , 28 ] (see Appendix A for definition of the marketing communication strategies) [ 5 ]. Development of the coding guidelines for messages was based on previous literature on e-cigarette marketing messages and the extracted content regarding messages delivered in the marketing communication strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Sebagai fungsi manajemen seorang petugas PR harus memiliki keahlian sebagai Creator, Conseptor, Mediator, Problem Solver (Poppy, 2014). Hasil penelitian yang dilakukan oleh Ukaj (2016) menunjukkan, PR memiliki identitas dan cara komunikasi yang spesifik dengan publik. Pelanggan setia perusahaan dan sebagian besar PR digunakan sebagai elemen komunikasi Integrated Marketing Communication (IMC) sebagai perpaduan antara pemasaran dan PR yang dikenal dengan MPR.…”
Section: Pendahuluanunclassified